Information needs and behaviour of humanities scholars in an ict-enriched environment in Jordan / Mohammad Khaled Issa Al Shboul - Mohammad Khaled Issa, Al Shboul (2016)

(untitled)
This study investigates information needs and behaviour of humanities scholars in an ICT-enriched environment in Jordan. The study was conducted at Yarmouk University, Jordan, one of the developing nations in the Middle East. Previous researches show that humanities scholars have a significant negative relation with ICT use although they demonstrate significantly higher use of library facilities compared to other academicians. There is also a lack of up-to-date research on information behaviour of humanities scholars that considers the recent rapid increase of ICT infrastructure and the emerging digital environment. Hence, the objectives of this study are to (a) understand the information needs and behaviour of humanities scholars in an ICT-enriched environment, (b) ascertain their information needs and information tasks, (c) identify the barriers they encountered, and (d) investigate the relationship between demographics information and information-seeking processes. The ultimate objective is to produce a model of information behaviour applicable to humanities scholars in the Arab nation. The conceptual model is based on integration of five models of information-seeking behaviour - Ellis, Kuhlthau, Wilson, Niedźwiedzka and Foster, with additional attributes representing the information context such as languages, decision to seek and format of information resources. The mixed-method approach was used where the qualitative approach involves face-to-face interviews with 26 scholars. A “factious, specific, concrete representations of target users”, known as Persona was used as the analysis method. For the quantitative approach, 280 humanities scholars were sampled in questionnaires survey where the descriptive, t-tests and chi-square statistics were used for analysis. The finding indicated that the humanities scholars have passive seeking behaviour which was triggered by information events. They also had different level of awareness regarding the availability of information sources and services in their areas of interest. In addition, the scholars had different motivations to iv seek information that could be determined by the use of appropriate format and understandable language. The junior scholars made an increasing use of digital resources while the senior scholars preferred printed materials and informal resources but give attention to digital resources. On the active information-seeking behavior, the humanities scholars had variant decision of information-seeking depending on their computer literacy, types and format of information needs. Furthermore, while they had different priority list on exploring, accessing, categorizing and purifying of information, their satisfaction was the same in all cases. The findings also showed barriers of library resources, university environment and personality had influenced their informationseeking and they reacted accordingly based on their experience and computer literacy. Simultaneously, while they were satisfied with the university library resources and services, they were not satisfied with the Centre of Excellence. Lastly, demographic data such as age, academic position, academic qualification and years of experience that differentiated between the senior and junior scholars showed significant correlation with types of information need and format. This study has provided a clear picture about the reality of humanities scholars’ information needs and behavior. This information is pertinent in providing excellent resources and services to reduce the barriers in information-seeking and to optimize the satisfaction level of the library users especially the electronic resources.